The Philosophy of William James: An introduction - M Gale, Richard (Cambridge University, 2013)
This is an accessible introduction to the full range of the philosophy of William James. It portrays that philosophy as containing a deep division between a promethean type of pragmatism and a passive mysticism. The pragmatist James conceives of truth and meaning as a means to control nature and make it do our bidding. The mystic James eschews the use of concepts in order to penetrate to the inner conscious core of all being, including nature at large. Richard Gale attempts to harmonize these pragmatic and mystical perspectives." "This introduction is drawn from and complements the author's much more comprehensive and systematic study, The Divided Self of William James. With its briefer compass and nontechnical style this new introduction should help to disseminate the key elements of one of the great modern philosophers to an even wider readership. Richard M. Gale is Professor Emeritus at the University of Pittsburgh and Adjunct Professor at the University of Tennessee, Knoxville.